Establishment and characterization of Asian oral cancer cell lines as in vitro models to study a disease prevalent in Asia - Sharifah Hamid; Kue Peng Lim; Rosnah Zain; Siti Mazlipah Ismail; Shin Hin Lau; Wan Mahadzir Wan Mustafa; M. Thomas Abraham; Noor Akmar Nam; Soo-Hwang Teo; Sok Ching Cheong (Spandidos Publication, 2024)
Volume 19 Issue 3